Developing Program Performance Measures for Rural Emergency Medical Services. (4th March 2017) - Gale, John; Coburn, Andrew; Pearson, Karen; Croll, Zachariah; Shaler, George
ABSTRACT: Background: The development of measures to monitor and evaluate the performance and quality of emergency medical services (EMS) systems has been a focus of attention for many years. The Medicare Rural Hospital Flexibility Program (Flex Program), established by Congress in 1997, provides grants to states to implement initiatives to strengthen rural healthcare delivery systems, including better integration of EMS into those systems of care.Objective: Building on national efforts to develop EMS performance measures, we sought to identify measures relevant to the rural communities and hospitals supported by the Flex Program. The measures are intended for use in monitoring rural EMS performance at the community level as well as for use by State Flex Programs and the Federal Office of Rural Health Policy (FORHP) to demonstrate the impact of the Flex Program.Methods: To evaluate the performance of EMS in rural communities, we conducted a literature search, reviewed research on performance measures conducted by key EMS organizations, and recruited a panel of EMS experts to identify and rate rurally-relevant EMS performance measures as well as emergent protocols for episodes of trauma, ST Elevation Myocardial Infarction (STEMI), and stroke. The rated measures were assessed for inclusion in the final measure set.Results: The Expert Panel identified 17 program performance measures to support EMS services in rural communities. These measures monitor the capacity of local agencies to collect and report quality and financial data, use the data to improve agency performance, and train rural EMS employees in emergent protocols for all age groups.Conclusion: The system of care approach on which this rural EMS measures set is based can support the FORHP's goal of better focusing State Flex Program activity to improve program impact on the performance of rural EMS services in the areas of financial viability, quality improvement, and local/regional health system performance.